2017
DOI: 10.1007/s00380-017-0961-z
|View full text |Cite
|
Sign up to set email alerts
|

General anesthesia improves contact force and reduces gap formation in pulmonary vein isolation: a comparison with conscious sedation

Abstract: Compared to conscious sedation (CS), the use of general anesthesia (GA) in pulmonary vein isolation (PVI) is associated with a lower recurrence rate of atrial fibrillation (AF). GA may improve catheter stability and mapping system accuracy compared to CS, but its influence on contact force (CF) parameters during ipsilateral PVI has not previously been investigated. The study population comprised 176 consecutive patients (107 in GA group and 69 in CS group) with AF who underwent their first PVI procedure. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…There was a lower number of PV reconnections found for those patients that underwent redo procedures in the GA group. Other studies have also shown that GA can lead to more stable catheter manipulation and better contact force and reduction of gaps 5 . The positive impact of GA on persistent AF ablation outcomes has been documented as well 6 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…There was a lower number of PV reconnections found for those patients that underwent redo procedures in the GA group. Other studies have also shown that GA can lead to more stable catheter manipulation and better contact force and reduction of gaps 5 . The positive impact of GA on persistent AF ablation outcomes has been documented as well 6 …”
Section: Discussionmentioning
confidence: 94%
“…Therefore, there is value in understanding and standardizing GA protocols with special consideration on the specific needs of EP procedures. Interestingly, the choice of anesthesia during AF ablation has been shown to affect long‐term outcomes 4‐6 . Hence, as we strive to standardize AF ablation procedures, special consideration should be given to the sedation or anesthesia protocol used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using catheters with contact-force, Chikata et al demonstrated that RFA in GA improves the contact force and thus increases the rate of PVI made by just one encircling lesion (first pass PVI) (50.5% vs. 34.8%, P=0.04) (ref. 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…RF catheter ablation was performed under general anesthesia or conscious sedation. The detailed procedure for anatomical ipsilateral PVI using an RF catheter has been previously described . In brief, an ablation catheter was used, and extensive encircling of ipsilateral PVI was performed under the guidance of 3D‐US geometries and 3D‐Merge CT using the CARTO 3 system (Biosense Webster).…”
Section: Methodsmentioning
confidence: 99%